Silence and praise: rhetorical cosmology and political theology in the Book of Revelation - Hansen, Ryan Leif (Emerging scholars, 2014)
Introduction -- "The apocalyptic technique" : how John's apocalypse makes meaning -- The war of worldcraft : John's cosmic rhetoric against Roman imperial cult discourse -- The three cycles of seven as object of interpretation -- Silence : the prayerful endurance and non-participation of the saints -- Praise : narrating the emergence of God's reign and the new creation -- Silence and praise : economic non-participation and narrating the new creation -- Toward an apocalyptic political theology